Interpersonal Dynamics in Assessment Center Exercises: Effects of Role Player Portrayed Disposition. (November 2016) - Oliver, Tom; Hausdorf, Peter; Lievens, Filip; Conlon, Peter
Although interpersonal interactions are the mainstay of many assessment center exercises, little is known about how these interactions unfold and affect participant behavior and performance. More specifically, participants interact with role players who have been instructed to demonstrate behavior reflecting specific dispositions as part of the exercise. This study focuses on role player portrayed disposition as a potentially important social demand relevant to participant behavior and performance in interpersonal simulations. We integrate interpersonal theory and trait activation theory to formulate hypotheses about the effects of role player portrayed disposition on participant behavior and performance in 184 interpersonal simulations. A significant effect of portrayed disposition was found for participant relationship building and directive communication behavior. Furthermore, portrayed disposition moderated the relationship between participant use of these behaviors and performance ratings. Conceptually, this study sheds light on the complementary mechanisms and social demands that produce participant performance differences across exercises. At a practical level, this study provides valuable evidence-based guidance for developing interpersonal simulations.